``Rodzina Działyńskich. |Archiwum Familijne'' - Archiwum Biblioteki Kórnickiej (1869-1923); Archiwum Główne Warszawa; Biblioteka Kórnicka; Piędzicki Adam, |Dom Bankowy Warszawa (1901)
Badowski Władysław, archiwista Archiwum Głównego w Warszawie, 1907-1913, (4), k. 6-8, 17. - Geppert Ignacy ks., proboszcz w Pakości, 1918-1919, (2), k. 18, 21-22. - Kaufmann Karl Josef, dyrektor Archiwum Państwowego w Gdańsku, 1913, k. 15-16. - Korzon Tadeusz, dyrektor Biblioteki Ordynacji Zamojskiej, 1913, k. 9-10. - Kozierowski Stanisław ks., 1919, k. 19-20. - Liedtke Franz ks., 1901. k. 1-2. -
13 listów
Keywords: Orle pod Wyrzyskiem; Runowo Krajeńskie; dwór; Warszawa; Dom Bankowy - Piędzicki Adam; Archiwum Główne; Korespondencja